PERAN INDUSTRI MANIK-MANIK TERHADAP PENYERAPAN TENAGA KERJA (Studi Kasus : Sentra Industri Manik-Manik Desa Plumbon Gambang, Kecamatan Gudo, Kabupaten Jombang) - Firdausi, Afini Fajrul (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims to determine and analyze the factors that may affect beads employment industry atPlumbon Gambang village, Gudo District, Jombang. Some factors are used to analyze the employment such as, wage levels, working capital, sales turnover and long effort. This research used multiple linear regression model or OLS (Ordinary Least Square) as the methods of data analysis. 40 beads business units are selected to participate in this study. The results of the data analysis shows that the variable wage (X1), venture capital (X2), sales turnover (X3) are gives positive and significant impact on employment, while the old variable effort (X4)give a significant negative effect on employment in beads industry of Plumbon Gambang village, Gudo District, Jombang.Keywords: employment, wages, capital, sales turnover, long effort.